Public Trust and the COVID-19 Vaccination Campaign: Lessons from the Philippines as it Emerges from the Dengvaxia Controversy - Mendoza, Ronald U (Archīum Ateneo, 2021)
While the entire world prepares and begins to roll out COVID-19 vaccines, the Philippines is still reeling from the consequences of the Dengvaxia controversy in 2016. Those highly political events led to the erosion of public trust in leaders and a significant damage to vaccine confidence in the country, now potentially impacting the uptake of COVID-19 vaccines. We discuss how public trust and confidence can be rehabilitated through accountability, transparency, and proper communication from the most trusted sources of the population. We also highlight key lessons for policymakers and leaders on allowing science to take the front seat, and politics behind, for the safety and well-being of the people during this public health crisis.